2021
DOI: 10.5811/westjem.2021.1.49652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Prescription Drug Monitoring Program on Emergency Department Opioid Prescribing

Abstract: Introduction Our goal was to determine whether implementation of a prescription drug monitoring program (PDMP) altered emergency department (ED) opioid prescription rates overall and in patients of different pain severities. Methods We conducted this single-center, retrospective review at an academic ED. The study examined patients discharged from the ED who received opioid prescriptions, before and after the state’s implementation of a PDMP (August 25, 2016). The month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Implementation of policies such as Prescription Drug Monitoring Programs has been linked to reductions in opioid use. 8 Our data suggest the hypothesis that the implementation of policy in North Carolina to address opioid prescribing may have had an impact on the relative number of hospital ED visits for NTDCs. As policy directed at opioid prescribing was implemented, the proportion of ED visits for NTDCs declined.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Implementation of policies such as Prescription Drug Monitoring Programs has been linked to reductions in opioid use. 8 Our data suggest the hypothesis that the implementation of policy in North Carolina to address opioid prescribing may have had an impact on the relative number of hospital ED visits for NTDCs. As policy directed at opioid prescribing was implemented, the proportion of ED visits for NTDCs declined.…”
mentioning
confidence: 64%
“…Naavaal et al 7 used more recent data from the 2015 to 2017 National Hospital Ambulatory Medical Care Survey and showed that dental visits were more likely to result in an opioid prescription relative to other conditions. Implementation of policies such as Prescription Drug Monitoring Programs has been linked to reductions in opioid use 8 …”
Section: Figurementioning
confidence: 99%
“…Less comprehensive PDMP legislation (allowing clinicians access to electronic PDMP data or mandating PDMP registration but not use) did not have as strong of an effect on the number of opioids prescribed or dispensed overall. Seven studies [45][46][47][48][49][50][51] found that less comprehensive PDMP legislation was associated with a decrease in the number of opioids prescribed or dispensed overall, whereas eight found no change [44,[52][53][54][55][56][57][58]. In total, 56 articles were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven states have a PDMP with 16 states mandating that it be utilized by prescribers. Studies have shown conflicting results regarding the effect that PDMP utilization has on opioid prescribing habits however, most show an overall decline in the amount of opioids prescribed in states with mandatory PMPs [ 21 23 ]. This survey of surgeons found that 62% of surgeons regularly use their state’s PDMP.…”
Section: Discussionmentioning
confidence: 99%